The Prospective Benefits of Using Machine Learning for the Prediction of Breast Cancer - Almofleh, Anwar; Alseddiqi, Mohamed; AlMannaei, Budoor; Najam, Osama; Atawi, Khamis (British Journal of Healthcare and Medical Research, 2022)
Improving the percentage of patients diagnosed with early-stage cancer is a vital priority of the World Health Organization. Cancer is one of the most unsafe diseases for humans, yet no enduring cure has been developed. Breast cancer is one of the most common types of cancer in the middle east region. Early diagnosis and treatment of breast cancer can significantly improve the lives of millions of women across the globe. Due to the advancement in technology, artificial intelligence and machine learning have been used successfully to discover several dangerous diseases, and serving in early analysis and treatment. Thus, the integration of artificial intelligence and machine learning in the scientific field supports enhancing morbity and mortality rates. This research is a systematic review on breast cancer discovery and action using genetic sequencing or histopathological imaging with the help of deep learning and machine learning.